2012
DOI: 10.1080/00071668.2012.674632
|View full text |Cite
|
Sign up to set email alerts
|

The thermostable β-1,3-1,4-glucanase fromClostridium thermocellumimproves the nutritive value of highly viscous barley-based diets for broilers

Abstract: 1. Microbial β-1,3-1,4-glucanases improve the nutritive value of barley-based diets for poultry by effectively decreasing the degree of polymerisation of the anti-nutritive soluble β-glucans. Glycoside hydrolases (GHs) acting on recalcitrant polysaccharides display a modular architecture comprising a catalytic domain linked to one or more non-catalytic Carbohydrate-Binding Modules (CBMs). 2. GHs and CBMs have been classified in different families based on primary structure similarity (see CAZy webpage at ht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…When normalized to a proportion of the total cellulolytic gene abundance, predicted proportions of β-1,4-endoxylanase were not significantly different between dietary groupings. Although not necessarily intuitive, these findings are supported by previous observations that the cellulolytic potential of the avian hindgut is minimal (Barnes, 1972; McNab, 1973; Mead, 1989), and correlates with the observation that cellulolytic pre-digestion of feed boosts energy harvest and weight gain (Józefiak et al, 2006; Yu et al, 2008; Cowieson et al, 2010; Mathlouthi et al, 2011; Ghahri et al, 2012; Ribeiro et al, 2012) in farmed broiler chickens. Caution must be taken in interpreting these predictions, as a recent study has shown that the functional capabilities of the gut microbiota are dependent on community membership as well as genetic potential (Berry et al, 2013).…”
Section: Resultssupporting
confidence: 78%
“…When normalized to a proportion of the total cellulolytic gene abundance, predicted proportions of β-1,4-endoxylanase were not significantly different between dietary groupings. Although not necessarily intuitive, these findings are supported by previous observations that the cellulolytic potential of the avian hindgut is minimal (Barnes, 1972; McNab, 1973; Mead, 1989), and correlates with the observation that cellulolytic pre-digestion of feed boosts energy harvest and weight gain (Józefiak et al, 2006; Yu et al, 2008; Cowieson et al, 2010; Mathlouthi et al, 2011; Ghahri et al, 2012; Ribeiro et al, 2012) in farmed broiler chickens. Caution must be taken in interpreting these predictions, as a recent study has shown that the functional capabilities of the gut microbiota are dependent on community membership as well as genetic potential (Berry et al, 2013).…”
Section: Resultssupporting
confidence: 78%
“…CtLic16A exhibits excellent enzymatic properties when expressed in E. coli [8,10], but expression in an industrial strain is a prerequisite for further commercial applications. Accordingly, the CtLic16A was expressed in the P. pastoris (P-CtLic16A) and its performances were examined and compared to that in E. coli (ECtLic16A).…”
Section: Ctlic16a Properties In P Pastorismentioning
confidence: 99%
“…Accordingly, CtLic16A is the most thermophilic and thermostable ␤-1,3-1,4-glucanase characterized to date. More recently, the E. coli produced CtLic16A has been proven effective as a commercial enzyme cocktail when supplemented in the broiler daily diet by reducing the digesta viscosity of the feedstuff, indicating that the enzyme is an attractive candidate to be developed as a commercial product [10]. Notably, the catalytic domain of CtLic16A shares a high sequence identity to Bacillus ␤-1,3-1,4-glucanases (38-57%), thus the structural features contributing to its extraordinary thermostability is an interesting topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…β-1,3-1,4-Glucanase is able to catalyze the hydrolysis of β-glucan into low molecular weight glucose polymers, thus reducing the hydrophilicity and viscosity of chyme and eliminating the anti-nutritional negative effect. Moreover, addition of β-1,3-1,4-glucanase can improve feed intake, enhance animal production, regulate cecal microbiota and increase feed conversion ratio [5][8]. Besides, the hydrolysis products from glucans—glucooligosaccharides may serve as fermentable dietary fiber-like substrates and positively affect gastrointestinal tract health [9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, commercial feed additive β-1,3-1,4-glucanases are generally from microbial expression systems, commonly Aspergillus japonicus [10], Pichia pastoris [11] and Clostridium thermocellum [8]. This process is flexible and convenient, but has disadvantages like high energy consumption, high equipment cost and serious environmental pollution.…”
Section: Introductionmentioning
confidence: 99%